Babesia ovis secreted antigen-1 is a diagnostic marker during the active Babesia ovis infections in sheep - Sevinc, Ferda; Zhou, Mo; Cao, Shinuo; Ceylan, Onur; Ulucesme, Mehmet Can; Ozubek, Sezayi; Aktas, Munir (Frontiers Media Sa, 2023)
Ovine babesiosis caused by Babesia ovis is an economically significant disease. Recently, a few B. ovis-specific proteins, including recombinant B. ovis secreted antigen-1 (rBoSA1), have been identified. Immunological analyses revealed that rBoSA1 resides within the cytoplasm of infected erythrocytes and exhibits robust antigenic properties for detecting anti-B. ovis antibodies. This protein is released into the bloodstream during the parasite's development. It would be possible to diagnose active infections by detecting this secretory protein. For this purpose, a rBoSA1-specific polyclonal antibody-based sandwich ELISA was optimized in this study. Blood samples taken from the naturally (n: 100) and experimentally (n: 15) infected sheep were analyzed for the presence of native BoSA1. The results showed that native BoSA1 was detectable in 98% of naturally infected animals. There was a positive correlation between parasitemia level in microscopy and protein density in sandwich ELISA. Experimentally infected animals showed positive reactions from the first or second day of inoculations. However, experimental infections carried out by Rhipicephalus bursa ticks revealed the native BoSA1 was detectable from the 7th day of tick attachment when the parasite began to be seen microscopically. Sandwich ELISA was sensitive enough to detect rBoSA1 protein at a 1.52 ng/ml concentration. Additionally, no serological cross-reactivity was observed between animals infected with various piroplasm species, including Babesia bovis, B. bigemina, B. caballi, B. canis, B. gibsoni, Theileria equi, and T. annulata. Taken collectively, the findings show that the rBoSA1-specific polyclonal antibody-based sandwich ELISA can be successfully used to diagnose clinical B. ovis infections in sheep at the early stage.
Keywords: BoSA1; cross-reaction; diagnosis; parasitemia; sandwich ELISA